Women at work, 1860-1939 : how different industries shaped women's experiences - Hall, Valerie G. (Regions and regionalism in history, 2013)
This book examines three different groups of women - in coal mining communities, in inshore fishing communities and in agricultural labour. It demonstrates how the work these groups undertook was fundamental in shaping their experiences as women in different ways and shows that women's experiences varied within class as well as between classes.